2009
DOI: 10.1080/01480540902882192
|View full text |Cite
|
Sign up to set email alerts
|

Antigenotoxic and antioxidant activities of isorhamnetin 3-O neohesperidoside fromAcacia salicina

Abstract: Antioxidant activity of isorhamnetin 3-O neohesperidoside (I3ON), isolated from the leaves of Acacia salicina, was determined by the ability of this compound to inhibit lipid peroxidation and to protect against hydroxyl radical-induced DNA damage in pKS plasmid DNA and Escherichia coli cultures. Antigenotoxic activity was assessed by using the comet assay. The IC(50) value of the inhibitory activity toward lipid peroxidation by I3ON is 0.6 mM. This compound was also able to protect against hydroxyl radical-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 39 publications
(37 reference statements)
0
7
0
2
Order By: Relevance
“…Previous studies have indicated that isorhamnetin exhibits anti-inflammatory and antitumor effects, and that it protects ventricular myocytes from ischemia and reperfusion injury (9)(10)(11). In addition, isorhamnetin has been reported to exhibit antioxidant properties (12)(13)(14). Choi (15) reported that isorhamnetin reverses H 2 O 2 -induced growth inhibition and exhibits scavenging activity against intracellular reactive oxygen species (ROS) in mouse-derived C2C12 myoblasts (15).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that isorhamnetin exhibits anti-inflammatory and antitumor effects, and that it protects ventricular myocytes from ischemia and reperfusion injury (9)(10)(11). In addition, isorhamnetin has been reported to exhibit antioxidant properties (12)(13)(14). Choi (15) reported that isorhamnetin reverses H 2 O 2 -induced growth inhibition and exhibits scavenging activity against intracellular reactive oxygen species (ROS) in mouse-derived C2C12 myoblasts (15).…”
Section: Introductionmentioning
confidence: 99%
“…Among the effective constituents, typhaneoside and I3ON are flavonoid glycosides. Researchers have revealed the antioxidant activities of I3ON, quercetin and kaempferol in this plant (Bouhlel et al 2009(Bouhlel et al , 2010Ye et al 2012;Surapaneni & Jainu 2014), but little attention has been paid to typhaneoside. Evidence from the available literature has shown that the antioxidant activity of the flavonoids is related to the number of hydroxyl groups on the B ring, especially the 3 0 -OH and 4 0 -OH groups; this observation is attributable to the addition of hydroxyl groups to carbon atoms in the ortho position, thereby enhancing the antioxidant capacity (Lago et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The pollen of Typha angustifolia, known as Puhuang in China, contains a variety of constituents including flavonoids (Jia et al 1986;Ishida et al 1988), stigmasterols (Della Greca et al 1990), fatty acids (Gallardo-Williams et al 2002), nucleosides (Tao et al 2012) and cerebrosides (Tao et al 2010). According to the pharmacological effects of these compounds, it has been suggested that flavonoids may play a major role as an antioxidant (Bouhlel et al 2009(Bouhlel et al , 2010. Besides, the constituents in the pollen have diverse biological effects, such as analgesic activity (Ma et al 2011), inhibition of the contractile activity of isolated uterus (Su et al 2010), and protection of the human umbilical vein endothelial cells against adrenaline-induced damage (Su et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…It has been a subject of numerous scientific studies which include clinical trials for cardiovascular diseases, type-2-diabetes, inflammation, memory impairment, oxidative stress, lipid metabolism disorders [23]. Isorhamnetin-3-O-neohesperidoside is a strong antioxidant with a potential to protect cells against oxidative stress [24].…”
Section: Lc-ms Guided Isolation Of Natural Products Was Carried Out Fmentioning
confidence: 99%